Colecionando livros, formando mestres: a Biblioteca Pedagógica da Escola Normal de São Paulo (1883) - Pestana, Marina Gugliotti (2011)
This work investigates the constitution of part of the collection acquired by Teacher Paulo Bourroul in traveling to France in the year of 1883 to integrate the library of the Normal School of São Paulo, considered the first one dedicated teachers´ formation in the city of São Paulo. The books brought to the 4th Chair - Methodology and Pedagogy - constitute our object and our main source for the realization of this research. The objective of this study was to survey the main pedagogical ideas that the books purchased by teacher Paulo Bourroul put into circulation and in this way know the models pointed by them for the teachers' training of the Normal School of São Paulo in the last quarter of the nineteenth century